PENERAPAN PEMBELAJARAN IPA BERBASIS COMPUTATIONAL THINKING MATERI SIKLUS AIR KELAS V SEKOLAH DASAR - Nur Azizah; Yohana Baptista; Christiyanti Aprinastuti (Prima Magistra: Jurnal Ilmiah Kependidikan, 2023)
This study aims to describe the application of computational thinking-based learning and its results. Through this research, it can be seen how to integrate computational thinking in learning as well as knowing students' abilities to use the foundation of computational thinking in the learning process. Research using descriptive method with a qualitative research approach. This research was conducted in the even semester of the 2022/2023 school year. The subjects in this study were 25 students in class V A at SD Kanisius Kadirojo, subdistrict Kalasan, Sleman, Yogyakarta. Data analysis in this study used student questionnaires, student worksheets, written tests, and interview guide sheets. From this research, it can be seen that computational thinking can be integrated into learning by using computational thinking foundations in solving problems according to learning materials. Learning in this study uses the foundation of pattern recognition, abstraction, and algorithms. Students can use these foundations indicated by 80% mastering pattern recognition skills, 72% mastering abstraction skills, and 100% mastering algorithm skills. The ability of students to understand learning material is also very good, shown by 76% of students passing the KKM. Students also feel happy with this computational-based learning and feel challenged by using the foundation